Cropsey [videorecording (DVD)] - Zeman, Joshua; Brancaccio, Barbara; Mortensen, Zachary (Breaking Glass Pictures : Vicious Circle Films, 2011)
Growing up in Staten Island, Joshua Zeman, Barbara Brancaccio and other kids had often heard the legend of the escaped mental patient 'Cropsey' who would come out late at night and snatch children off the streets. Urban legend was turned upside down in the summer of 1987 when a little girl with Down syndrome disappeared from their neighborhood. Two filmmakers delve into the mystery behind five missing children and the real-life bogeyman linked to their disappearances in their hometown of Staten Island, New York.